Microscopic detection of hemozoin in peripheral leukocytes fails to indicate plasmodial placental infection in pregnant women (2017)
ABSTRACT: Introduction: Malaria in pregnancy very often includes gestational (parasites in maternal peripheral blood) and placental (parasites in placental blood) infection, but the later condition can only be detected after delivery. High frequency of placental plasmodial infection has been confirmed in many countries and is associated with negative birth outcomes. With the hypothesis that placental infection is accompanied by hemozoin circulation in maternal peripheral blood, an exploratory study was conducted to evaluate the association between peripheral leukocytes with hemozoin and placental infection by Plasmodium vivax or Plasmodium falciparum in parturient women. Methodology: A descriptive, transversal and exploratory (pilot type) study was carried out with women from two malaria-endemic localities of northwest Colombia. A total of 25 parturient women with confirmed placental infection and 25 without placental infection were included. Two independent readers measured the number of leukocytes with hemozoin in thick smears of maternal peripheral blood. Plasmodial infection in maternal peripheral blood and placental blood was detected by thick smear and quantitative polymerase chain reaction (qPCR). Results: Four parturient women had leukocytes with hemozoin in peripheral blood; three of them had placental plasmodial infection and one was negative for placental infection. No statistically significant association between leukocytes with hemozoin in peripheral blood and placental infection was observed. Conclusions: With this limited sample size, detection of leukocytes with hemozoin by thick smear of maternal peripheral blood did not indicate presence of placental infection.